Clinical Chronicles: A Case Report on Pink Tooth of Mummery - Kriplani, Simran; Mahapatra, Joyeeta; Sedani, Shweta; Ikhar, Anuja; Patel, Aditya (Iranian Endodontic Journal, 2024)
Internal tooth resorption is a subtle proceeding typically occurring in the tooth dictating past trauma, chronic pulpal inflammation, or caries-related issues. It is frequently observed Front teeth are susceptible to injury because they are more vulnerable but can also affect posterior teeth, often due to pulp involvement in cavities. Timely detection, addressing the underlying cause, and Effective care of the impacted root are essential for achieving a favorable treatment result. This case report illustrates the handling of a resorptive issue in the lower part of the tooth, managed through non-surgical means employing the thermoplasticized gutta-percha technique.